Radioisotopic evaluation of bone repair after experimental surgical trauma Avaliação radiofarmacológica do reparo ósseo após trauma cirúrgico padronizado - Ana Cristina Breithaupt-Faloppa; Pedro Fernandes Lara; Marinilce Fagundes dos Santos; Ricardo Martins Oliveira-Filho; Oswaldo Crivello Junior (University of São Paulo, 2004)
BACKGROUND: Scientific approach of the bone reaction after surgical procedures provides valuable information on methods and techniques. The purpose of this study was to follow this process using a radioisotope marker of bone remodelling. MATERIAL AND METHODS: Two bone cavities were created (one for every tibia) in adult Wistar male rats using a 0.5 mm spherical burr; left tibial cavities were filled with bovine freeze-dried bone; the right ones were left unfilled for control. Scintigrams were done with sodium methylene diphosphonate (MDP) labelled with radioactive pertechnetate (99mTcO4-) to evaluate the inflammatory response and the local osteoblastic activity. The evolution of bone repair was additionally evaluated by light microscopy. RESULTS: Our results have shown that the highest bone activity was recorded between the 7th and the 14th day after surgery. The morphological analysis confirmed the results obtained with radioisotope analysis and did not reveal significant differences regarding the evolution of bone repair between the filled and the unfilled defects. CONCLUSION: We confirmed that 99mTc -MDP is a valuable tool to study bone repair, as it was able to show subtle alterations of bone activity even in lesions as small as those created herein (0.5 mm wide, 0.5 mm deep). Este trabalho objetivou estudar a evolução temporal do processo de reparo ósseo em tíbia de rato, após trauma cirúrgico padronizado. A incorporação do radiofármaco 99mTc-MDP na região afetada foi tomada como medida indireta da intensidade de reação tecidual; foi feito também acompanhamento histológico do processo de reparo. Foram realizadas cirurgias nas duas tíbias de 72 animais divididos em 2 grupos, sendo sacrificados em diferentes dias pós-operatórios (1, 3, 7, 14, 21 e 28 dias p.o.). As cavidades criadas nas tíbias esquerdas foram preenchidas com osso liofilizado bovino, e as direitas serviram como controle (não preenchidas). Grupos paralelos de animais foram injetados com 99mTc para avaliar a influência do fluxo sangüíneo regional nos resultados. Duas horas após a injeção dos radiofármacos os animais foram sacrificados, a radiatividade foi contada tanto nos fragmentos das tíbias contendo os defeitos cirúrgicos como em fragmentos intactos de fêmur e de tíbias, como controle. Os resultados indicam que a maior atividade do tecido ósseo ocorreu entre 7 e 14 dias p.o. O emprego do radiofármaco mostrou ser de valor na avaliação do reparo dada sua sensibilidade. Não houve efeito significativo da presença de osso liofilizado sobre a evolução do reparo ósseo.